Campaign education and communication to the potential consumers of brewers’ spent grain (BSG)-added food products as sustainable foods - Naibaho Joncer; Korzeniowska Małgorzata; Julianti Elisa; Sebayang Nico Syahputra; Yang Baoru (Elsevier Ltd, 2026)
Byproduct of the brewery industry, brewers’ spent grain (BSG), has been reported for enhancing the nutritional value of food products thus potentially as a future sustainable food ingredient. As it is a byproduct, society as potential consumers tend to consider BSG as waste. Consequently, commercialization of BSG-added food products would be responded negatively by potential consumers. Campaign education seems to be important in order to familiarize such products to the society thus change the consumers perspective and finally increase the consumers acceptability. This study, which was conducted by an online survey platform (surveymonkey.com), aims to educate the society about the positive value of BSG for human health and its valorisation to the environment which generates sustainable food and to observe their opinion and expectation regarding such products. Majority of participants (57.38%) never knew BSG before. After BSG was introduced, most of the provided information about BSG is new for the majority of participants and they are convinced that consuming BSG-added food products would be beneficial for their health and help a sustainable environment. Furthermore, if such products are claimed as healthy foods, 81.97% of the participants are willing to buy. Besides the mindset of consumers, several issues might need to be considered in commercializing BSG-added food products including food regulation and safety as well as specific health conditions. Further study is still needed in order to educate society in a wider and to be specific in certain groups of community.